An ecofriendly dyeing of wool with supercritical carbon dioxide fluid. (1st February 2017) - Zheng, Huanda; Xu, Yanyan; Zhang, Juan; Xiong, Xiaoqing; Yan, Jun; Zheng, Laijiu
Abstract: Dyeing feasibility of wool was investigated with Disperse Red 54, Disperse Blue 183, Disperse Red 153, Disperse Blue 148, Disperse Red 92, and Disperse Yellow 82 in supercritical carbon dioxide. The effects of dyeing temperature, pressure, time, dye mesh number, as well as CO2 flow on the K/S values and fixation rates of the wool samples were discussed. The results showed that the higher K/S values and fixation rates were obtained with Disperse Red 153 and Disperse Blue 148 in comparison with other disperse dyes. Simultaneously, the K/S values and the fixation rates were improved gradually from 70 °C to 110 °C, 15 MPa to 25 MPa, 60 min to 120 min, as well as 40 mesh number to 100 mesh number for Disperse Red 153, and from 80 °C to 120 °C, 15 MPa to 25 MPa, 60 min to 120 min, as well as 40 mesh number to 100 mesh number for Disperse Blue 148 during supercritical carbon dioxide dyeing procedure. Moreover, excellent permeability and color fastness were obtained whereas the breaking force and tensile strength of the dyed wool fibers were reduced slightly after supercritical carbon dioxide dyeing. Graphical abstract: Highlights: Two thiazole dyes were selected from six disperse dyes with different structures. It is feasible to achieve ecofriendly dyeing of wool with Disperse Red 153 and Disperse Blue 148. Dyeing performance of wool was investigated in supercritical CO2 . The effects of different dyeing parameters on the K/S value and fixation rate were discussed. The excellent permeability, acceptable color fastness and mechanical properties were obtained.